Sensory Profile Characterization of Commercial Tea and Kombucha Beverages Using Flash Profile and Check-All-That-Apply (CATA) Methods - Tsania Rizqiya Rahawarin; Hadi Munarko; Andre Yusuf Trisna Putra; Ajeng Astrini Brahmanti (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2026)
Tea-based beverages continue to evolve in response to growing consumer demand for healthier, more diverse drink options. Among these products, conventional brewed tea and kombucha represent two categories with distinct processing methods and sensory characteristics. Brewed tea is generally appreciated for its familiar taste and mild flavor, whereas kombucha offers a more complex sensory profile due to fermentation processes involving organic acid production and carbonation. Understanding consumer perception toward these beverages is important for product development and market positioning. This study aimed to characterize the sensory attributes of commercial tea and kombucha beverages and to evaluate consumer preference using rapid sensory profiling methods. Six commercial beverage samples, consisting of brewed tea and kombucha products, were analyzed using Flash Profile and Check-All-That-Apply (CATA) methods. Flash Profile evaluation was conducted by semi-trained panelists, while CATA assessment involved consumer respondents to capture product perception and preference patterns. The results showed clear sensory differentiation between brewed tea and kombucha beverages. Brewed tea products were generally associated with sweetness, tea aroma, brown appearance, and lighter mouthfeel, while kombucha samples were characterized by sourness, fermented aroma, sparkling sensation, and lingering acidity. Consumer preference analysis indicated that Kombucha D was closest to the ideal product due to its balanced sensory profile, particularly clarity, smoothness, and sweetness, and its lower dominance of sharp, fermented, and acidic attributes. The combination of Flash Profile and CATA provided complementary information for rapid beverage evaluation and may serve as a practical approach for sensory-based product development in the beverage industry. Contribution to Sustainable Development Goals (SDGs):SDG 3: Good Health and Well-BeingSDG 9 : Industry, Innovation and InfrastructureSDG 12: Responsible Consumption and Production